The Role of Agricultural Extension in Improving the Productivity of Local Corn Farming in Siompu District, South Buton Regency - Azizu, Azelia Monica; Azizu, Muhamad Noor (Tarjih : Agribusiness Development Journal, 2025)
This study investigates the role of agricultural extension in enhancing productivity of local maize farming systems in Siompu District, South Buton, an island ecosystem characterized by shallow sandy–coral soils and a dominant smallholder strategy combining maize cultivation and goat husbandry. Using a quantitative survey complemented by qualitative field observations, data were collected from 82 maize farmers selected through stratified random sampling. Four variables were examined: (1) effectiveness of extension services, (2) adoption of site-specific maize cultivation technologies, (3) integration of maize–goat farming, and (4) maize productivity. Results indicate extension performance is moderate, constrained by infrequent visits and limited use of field demonstrations. Technology adoption is also moderate; farmers readily adopt low-cost practices such as improved row spacing and organic fertiliser, but show low uptake of key soil and water conservation measures, including mulching, minimum tillage, and balanced fertilisation, which are crucial for sandy soils. The maize–goat integration index shows strong use of goat manure and maize residues, yet integration remains traditional and falls short of zero-waste nutrient cycling. Regression analysis shows technology adoption has the strongest effect on productivity, followed by farming-system integration and extension performance. Overall productivity remains low due to partial agronomic innovation uptake and suboptimal livestock-resource integration. The study recommends a more intensive, site-specific, and integrated extension model that prioritises soil conservation technologies aligned with existing maize–goat practices to strengthen sustainable maize production in small-island dryland agroecosystems. Government seed support is limited and irregular, strongly reinforcing farmers’ reliance on locally sourced seed.